Pengaruh Pengalaman Magang, Pengetahuan dan Kesadaran Finansial terhadap Preferensi Mahasiswa terhadap Lembaga Keuangan Syariah. - Alfitri Wulandari; Nur Fadhillah; Dwi Afrianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of internship experience, knowledge and financial awareness on the preferences of Islamic financial institutions (student study of the Faculty of Economics and Islamic Business, Qomaruddin University, Gresik) in choosing Islamic financial institutions. This background is based on the importance of the role of the younger generation as potential customers and workers in the development of the Islamic financial industry in Indonesia. This study uses a quantitative approach with a survey method through a questionnaire to 50 respondents selected by purposive sampling. Data analysis was carried out using multiple linear regression. The results of the study indicate that partially, internship experience, knowledge and financial awareness each have a significant effect on the preferences of Islamic financial institutions. Simultaneously, the three variables also have a significant effect on student preferences. These findings are expected to be input for educational institutions, Islamic financial institutions, and related parties in increasing literacy and interest of the younger generation in the Islamic financial sector.